A non-rare earth ion doped broadband emission phosphor located in NIR-II for ethanol concentration detection. Issue 35 (23rd August 2022) - Ye, Zejun; Wang, Zhijun; Yang, Huifang; Huo, Xiaoxue; Wang, Yu; Wu, Qian; Wang, Dawei; Zhao, Jinxin; Suo, Hao; Li, Panlai
Abstract : Ca2 GeO4 :Cr presents NIR-II emission (1000–1700 nm) with a FWHM of 215 nm. Abstract : In this work, a new NIR phosphor Ca2 GeO4 : x Cr was developed, whose emission range (1000–1700 nm) is well within NIR-II, with a full width at half maximum (FWHM) of 215 nm. Interestingly, by sintering under an air atmosphere, the Cr 3+ ions in the raw material are oxidized to Cr 4+, and the near-infrared light emitted by the material is not the usual luminescence of Cr 3+ ions located in NIR-I, which can be attributed to the dominant substitution of Cr 4+ ions doped into the lattice sites. A pc-LED fabricated with this phosphor can detect different concentrations of ethanol, which demonstrates its good potential for non-destructive testing applications.